Odpowiedź :
Ek=20000 J
m=0,16kg
Ek=mv²/2 /×2
2Ek=mv² /m
2Ek/m=v² /√
√2Ek/m=v
v=√2×20000÷0,16
v=√40000:0,16
v=√25000
v=500m/s
m=0,16kg
Ek=mv²/2 /×2
2Ek=mv² /m
2Ek/m=v² /√
√2Ek/m=v
v=√2×20000÷0,16
v=√40000:0,16
v=√25000
v=500m/s
m=0,16kg
Ek=20000J
Ek=mv^2/2 |*2
2Ek=mv^2 |:m
v^2=2Ek/m
v^2=2*20 000J/0,16kg = 40 000J/0,16kg=250 000 m/s
v=250 000 (pod pierwiastkiem 250 000)
v=500 m/s
Ek=20000J
Ek=mv^2/2 |*2
2Ek=mv^2 |:m
v^2=2Ek/m
v^2=2*20 000J/0,16kg = 40 000J/0,16kg=250 000 m/s
v=250 000 (pod pierwiastkiem 250 000)
v=500 m/s
Ek = (mV^2)/2
m - masa
V - predkosc
Ek - energia kinetyczna
Z pierwszego wzoru:
V = pierwiastek (2Ek/m)
V = pierwiastek (40 000/0,16)
V = pierwiastek (250 000)
V = 500 [m/s]
m - masa
V - predkosc
Ek - energia kinetyczna
Z pierwszego wzoru:
V = pierwiastek (2Ek/m)
V = pierwiastek (40 000/0,16)
V = pierwiastek (250 000)
V = 500 [m/s]